Developing nurse and midwife centred rostering principles using co-design: a mixed-methods study - Sara Holton; Bodil Rasmussen; Karrie Long; Madison Bellizia; Jac C. Mathieson; Shane Crowe; Douglas Mill; Harry Pasion; Claire Rankin; Maree Woodhouse; Meaghan Douglas; Nadine Glanville; et al. (BMC Nursing)
Abstract Background Current nursing and midwifery rosters are based on guidelines which may no longer adequately meet the needs of health services or staff and often result in decreased job satisfaction, poor health and wellbeing, and high turnover. Little is known about the rostering needs and preferences of contemporary nurses and midwives in Australia. The aim of this study was to identify the rostering concerns, needs and preferences of nurses and midwives, and co-design acceptable, equitable and feasible rostering principles. Methods A mixed-methods design using a co-design approach with three components: survey, discussion groups, and co-design workshops. Nurses and midwives employed at three public health services in Victoria, Australia were invited to participate. The quantitative (survey) data were analysed using descriptive statistics and the qualitative (discussion groups and co-design workshops) data using thematic analysis. Results Surveys were completed by 715 nurses and midwives including unit (n = 14) and roster (n = 13) managers. Nurses and midwives (n = 688) were mostly satisfied with their roster (mean satisfaction score = 57.4). Many had responsibilities or commitments which impacted their roster availability (n = 406, 61.6%) and over half had taken personal leave due to roster-related fatigue (n = 335, 59.1%) or unmet roster requests (n = 310, 54.7%). Midwives reported significantly less satisfaction (p < 0.001) and more challenges with current roster practices than nurses. Roster and unit managers described spending considerable time preparing and reworking rosters. Thirty-nine nurses and midwives participated in a focus group and outlined concerns about the fairness and equity of current roster practices, and the adverse impact on their health, work, and personal lives. Ninety-one nurses and midwives participated in a co-design workshop and identified a need for roster practices and guidelines which ensure flexibility, fairness and equity, and fatigue management. Conclusions Although nurses and midwives were mostly satisfied with their rosters, they often experienced frustrations and challenges with current roster guidelines and practices as well as adverse effects on their health and work and personal lives. Nurses and midwives identified a preference for fair and equitable rosters which provide flexibility and enable them to manage their other commitments and responsibilities, reduce roster-related fatigue, and provide high quality patient care.